The Battle of Truths: The Production of Meaning in Indonesian Political Memes - Agustinus Dias Suparto (Institute of Research and Community Outreach - Petra Christian University, 2018)
Memes have been used in the public discussion nowadays by the internet users and the emergence of social media especially Instagram has facilitates people to share their opinions. Thus, people are trying to influence each other using memes about the political tension which involves Basuki Tjahaja Purnama about his blasphemy case on Islamic verse in Al Quran and Habib Rizieq’s case. Therefore, in order to influence other using memes, several iconic figures are used to produce the meaning about the truths that are said by those figures in each faction. The using of news as the valid data to represent the reality is also used to be the truth that should be believed by the readers of the memes. Later, this paper will try to analyze using discursive approach on how memes use several features to convince the readers to believe that the meaning in the memes is the truth. Finally the memes from two political factions which are pro and cons about the cases are used to reveal the meaning production in memes.